2021
DOI: 10.1002/ppul.25652
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive sleep apnea and metabolic disorders in morbidly obese adolescents

Abstract: Background Little known about the prevalence of obstructive sleep apnea (OSA) in morbid obese adolescents and the association between OSA and comorbid factors. Aim To examine the association between apnea–hypopnea index (AHI, a measure for OSA severity) and metabolic morbidity among morbidly obese adolescents. Methods We performed a population‐based retrospective cohort study by reviewing sleep study, metabolic indices, and comorbidity‐related data of a cohort (n = 106) of adolescents referred to a bariatric s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…As shown by Redline et al, 15 OB is a strong risk factor for adult OSA, and is also a major risk factor for snoring or OSA in pediatric populations 35,44,45 . Accordingly, as illustrated in Table 2, we found significant differences between the OB prevalence of children with resolved OSA after treatment and those with persistent disease.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As shown by Redline et al, 15 OB is a strong risk factor for adult OSA, and is also a major risk factor for snoring or OSA in pediatric populations 35,44,45 . Accordingly, as illustrated in Table 2, we found significant differences between the OB prevalence of children with resolved OSA after treatment and those with persistent disease.…”
Section: Discussionsupporting
confidence: 67%
“…27 Finally, there is also relevance in evaluating the association between OB, OSA, and MetS. 15,19,30,35 Therefore, children with body mass index (BMI) z-score values exceeding the 95th percentile were classified as fulfilling the criteria for OB, following the recommendations of the Centers for Disease Control and Prevention (https:// www.cdc.gov/obesity/basics/childhood-defining.html).…”
Section: Definition Of Metsmentioning
confidence: 99%
“…The results from multivariate linear regression showed that BMI, the width of the nasal base, and SNA seemed to have significant influences on the severity of OSA. The impacts of obesity on development and severity of OSA have been well-known [ 50 , 51 ]. Maxillary protraction may lead to increased nasopharyngeal and upper oropharyngeal dimensions and an improvement in sleep apnea [ 13 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to obesity, the important perturbations of iron metabolism may be linked to the progression of OSA. There are many studies on iron metabolism and OSA [ 12 , 13 , 14 , 15 ], but only limited studies focus on body iron transport as reflected by serum TF levels and the results are controversial. Baik et al [ 16 ] indicated that OSA cases showed lower serum TF saturation levels than those without OSA no matter with male-pattern baldness or not.…”
Section: Introductionmentioning
confidence: 99%